Rola Prezesa Urzędu Zamówień Publicznych w zapobieganiu i zwalczaniu nadużyć wolności kontraktowej w umowach zawieranych w ramach zamówień publicznych - Sołtys, Bogusław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The study examines the actual and postulated role of the Chairman of Public Procurement Chamber in prevention and eradication of freedom of contract abuse, which is not directly related to the infringement of public procurement law but civil law and other law branches. The issue has not been analyzed by the doctrine, even though the practice of contracting authorities in public procurement standard agreements often leads to freedom of contract abuse, which is tolerated by the Chairman of Public Procurement Chamber. Taking into consideration the dimension of detrimental results not only for the economy but also public finance, the body which supervises the public procurement market should have broader competences. Localizing all the protection against unfair and illegal standard agreement provisions only in courts of law as well as relinquishment of the prevention measures is an ineffective, inappropriate and systemically unjustified solution.
Keywords: Prezes Urzędu Zamówień Publicznych; prawo zamówień publicznych; naruszenie prawa; ochrona